Tracing cultural ties of carpet weaving in Kazakhstan and Central Asia - Kasenova, Kyzdarkul B. (Opción, 2020)
The diverse culture of Kazakhstan has long been the fruitful soil for the flourishing of the unique handicraft of carpet weaving. Kazakh traditional carpet weaving of the 19th – early 21st centuries, comprising the peculiar ethnic identity, vivid artistic expressiveness and deep spiritual meaning, necessitates its comprehensive study. The in-depth study of formation and evolution of artistic traditions of the Kazakh carpet weaving by analyzing the archive data and museum collections will enable a thorough study of this tradition, and the history and social and cultural ties of the Kazakh people, its philosophy and values that were reflected in carpet ornaments.